2022
DOI: 10.1038/s41598-022-24157-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lung and lobe volumes between supine and upright computed tomography in patients with idiopathic lung fibrosis

Abstract: No clinical study has compared lung or lobe volumes on computed tomography (CT) between the supine and standing positions in patients with idiopathic lung fibrosis (IPF). This study aimed to compare lung and lobe volumes between the supine and standing positions and evaluate the correlations between the supine/standing lung volumes on CT and pulmonary function in patients with IPF. Twenty-three patients with IPF underwent a pulmonary function test and both low-dose conventional (supine position) and upright CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Owing to concerns regarding transmission, COVID-19 complicates the assessment of pulmonary function in the acute phase 34. Previous reports showed that CT-derived lung volume strongly correlated with the pulmonary function test results 8 9. Therefore, CT-derived lung volume could serve as a surrogate marker for the physiological assessment of COVID-19 in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to concerns regarding transmission, COVID-19 complicates the assessment of pulmonary function in the acute phase 34. Previous reports showed that CT-derived lung volume strongly correlated with the pulmonary function test results 8 9. Therefore, CT-derived lung volume could serve as a surrogate marker for the physiological assessment of COVID-19 in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Previous reports showed that CT-derived lung volume strongly correlated with the pulmonary function test results. 8 9 Therefore, CT-derived lung volume could serve as a surrogate marker for the physiological assessment of COVID-19 in the acute phase. In this study, patients with decreased lung volume exhibited a higher incidence of multiorgan complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROG represents an estimated mean opacity value of parenchymal abnormalities, which was calculated for each patient by summing the values for all lobes and dividing them by five (the total number of lobes). The middle lobe values were given half the weight of the other four lobes ( 14 ). The patients were grouped by opacity extension at 10 months in either the low-ROG group with no or only minor opacities on CT (up to 5%, n = 37) or in the high-ROG group with more widespread opacities (>5%, n = 81) and moderate-to-severe opacities.…”
Section: Methodsmentioning
confidence: 99%
“…These disorders are varied in character with overlapping clinical manifestations, making proper diagnosis and monitoring extremely difficult. In the field of respiratory medicine, high-resolution computed tomography (HRCT) has become a crucial instrument, providing unmatched insights into the complex structural alterations linked to a range of interstitial lung disorders [2]. We also investigated the finer points of HRCT imaging in order to clarify its monitoring and diagnostic use with respect to ILDs.…”
Section: Introductionmentioning
confidence: 99%